Supplementation of nano-bubble curcumin extract improves gut microbiota composition and exercise performance in mice. Issue 4 (9th April 2020) - Chen, Yi-Ming; Chiu, Wan-Chun; Chiu, Yen-Shuo; Li, Tong; Sung, Hsin-Ching; Hsiao, Chien-Yu
Abstract : NCE supplementation was able to modulate the gut microbiota increased the Lactobacillus genus. Abstract : Background : In a previous study, we evaluated the potential beneficial effect of nano-bubble curcumin extract (NCE) in reducing exercise-related injuries and improving performance. Methods : In this study, we seek to investigate changes in the gut microbiota composition upon NCE supplementation in relation to health and exercise performance. Male ICR mice were divided into 3 groups ( n = 8 per group) and orally administered NCE once daily for six weeks at 0 (vehicle), 3.075 (NCE-1X) and 15.375 g kg −1 day −1 (NCE-5X). The gut microbiota from the mice was analyzed using 16S rRNA gene sequencing. Results : NCE-5X did not appear to obviously cluster with the vehicle group, although NCE-5X groups showed an increased Firmicutes/Bacteroidetes ratio compared with the vehicle group. In addition, anti-fatigue activity and exercise performance were evaluated by investigating the exhaustive swimming time, forelimb grip strength and serum levels of lactate, ammonia, glucose, blood urea nitrogen (BUN), creatine kinase (CK) and lactate dehydrogenase (LDH) after swimming. The NCE-1X and NCE-5X groups showed a significantly longer exhaustive swimming time and higher relative forelimb grip strength than the vehicle group. Tissue glycogen content, an important energy source for exercise, increased significantly with NCE supplementation. Conclusion : Taken together, our results indicate that NCE supplementation alters the gut microbiota composition and aids in overcoming physical fatigue. Curcumin may be acting on the gut microbiome to modulate the gut system towards improving exercise performance.